Quintas do Douro : arquivos e investigação histórica - Pereira, Gaspar Martins (2003)
In spite of the efforts made in the last two decades, we are still far from possessing a well established perspective of the long history of the wine cultivation in the Demarcated Region of Douro on the contrary of what happens concerning other regions of production. The development of the historical investigation about the vine-grower Douro implies the inventorying, preservation and creation of study conditions of documents, traditionally despised by the investigators, in particular family archives and those of firms connected with the historical farms of the region. It will be, thus, possible to change some of the more ordinary mistakes in the history of the Port wine and its region of origin: the space mistake that has made the history of the vineyard and of the Port wine dependant of the vicissitudes of the exporter circuit, with headquarters in Oporto and Gaia, despising the analysis of the social structures, of the production technology and of the evolution of the production in the vine-grower region; the chronological mistake that has limited the history of the Douro wines from the statistics of exports to England, from the end of the seventeenth century, as if only then it was started the production of wine with quality in the region; the method mistake that, due to the difficulty to have access to direct sources of information about the production, has been limited to the use of inference indicators or even to the spreading for the Douro region of information available for other vine-grower regions.